Enhancing student learning motivation: Developing an integrated mathematics module with islamic values - Hifzhi, Husnul; Asmar, Ali; Fauzan, Ahmad; Jamaan, Elita Zusti (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: The teaching of mathematics in Islamic schools has not yet succeeded in attracting and motivating students to learn. The lack of relevant context and meaningful values in the teaching materials can lead to low student motivation. Integrating Islamic values into mathematics learning modules is expected to provide more meaningful, relevant learning experiences and increase students' motivation to learn.Aim: This study aims to produce a mathematics module integrated with Islamic values to enhance students' learning motivation. The module is designed to meet the criteria of being valid, practical, and effective.Method: This research employs the Plomp development model, which consists of three stages: preliminary stage, development stage, and assessment stage. The developed module has been validated by experts in content, language, and media.Result: The implemented module meets the criteria of validity, practicality, and effectiveness. The module is valid with an average score of 88.9%, practical with an average score of 89.7%, and effective in improving students' mathematics learning outcomes, with 86.67% of students achieving mastery. The module also successfully increased students' learning motivation, with 84.50% of students showing improved motivation.Conclusion: Based on these results, it can be concluded that the mathematics module integrated with Islamic values is valid, practical, and effective.